Real-time digital twin for ship operation in waves. (15th December 2022) - Lee, Jae-Hoon; Nam, Yoon-Seo; Kim, Yonghwan; Liu, Yuming; Lee, Jaehak; Yang, Heesuk
Abstract: This paper introduces a real-time digital twin for ship operations in seaways. The concept of the digital twin is becoming popular, and it is adopted for ship operation systems in this study. In particular, this paper introduces a new and innovative concept of the digital twin to predict ocean waves and hydrodynamic performances, such as seakeeping and maneuvering, which enables the risk and optimum route to be forecast in real time. An essential element in the realization of such a real-time digital twin is the real-time prediction of ocean waves. Hence, a sophisticated algorithm for wave reconstruction using measured wave-radar images is developed, which is extended to predicting the future evolution of a three-dimensional wave field in front of a ship within a time window of the order of 10 min. As another essential element, an analysis program to solve the coupled seakeeping-maneuvering problem is developed. This analysis can also be used in real time. By combining this with wave prediction software, the future occurrence of ocean waves and ship responses can be predicted. By extending this approach, the risk and performance of ships in various ocean environments can be predicted. In this paper, concepts, approaches, and examples are introduced. Highlights: This paper introduces an innovative concept of a real-time digital twin for ship operations in seaways. Modules for wave prediction, ship hydrodynamics, and navigation control are integrated. The reconstruction and prediction of wave field are investigated considering ship operations. Real-time predictions for ship operation and future risk within a few tens of minutes are validated. The operation guidance is established based on the predicted resistances and significant motions.